IMPLEMENTASI KEBIJAKAN ALIH FUNGSI PENGGUNAAN LAHAN DI LEMBAH SUNGAI TAMBAK BAYAN KABUPATEN SLEMAN - , Tree Setiawan Pamung ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The theme of this research takes the land use change in Tambak Bayan rivers valley. Where the problems raised depart from a failure of the implementation of the IPPT policy aimed at controlling the land use that is not required of it. In this research highlight more deeply about the land use change in Tambak Bayan rivers valley that is water catchment area into land used for the construction of MC with the concept of superblok. In this research is the study of public policy implementation which highlights the policy implementation of the sustainable Development paradigm. In this case there are three aspects that are becoming major concerns, i.e. environmental aspects, social aspects and economic aspects in terms of the land use in Tambak Bayan rivers valley. This research is qualitative research. Based on the results of research conducted by the author there are some findings, the environmental and social sectors, the paradigm is built that happens a decrease or loss in the field of the environment. In terms of policy, environmental and social sectors earned a portion of that is quite high, but in the process of implementation of the environmental and social fields do not match. The impact caused to the environmental and social sectors are negative which is vulnerable to environmental and social disaster. In economics, the paradigm built indicate positive benefits. In the aspect of economic policy was less cared for. While the perceived economic impact of absorption of labor as much as 504 people and any investment. Things that affect the implementation of the land use functions in Tambak Bayan rivers valley that the power elite interests, behavior and implementor, service procedures and limitations of human resources.